Increasing Public Awareness of Financial Planning through Life Insurance Education: An Effort to Promote a Sustainable Economy in Indonesia - Utami, Nabela; Fadil, Cholid; Imaningsih, Niniek (Pascasarjana Universitas Mataram, 2025)
One of the most important factors in a healthy private financial study is literacy, especially among Indonesian people who still have a low level of understanding. The purpose of this study is to increase public awareness of financial literacy through mental education which is considered capable of improving the ongoing economic conditions. The methods used are seminars and canvas campaigns to provide information about financial literacy and the value of insurance for children. The results of the program show that there is an increase in student awareness, especially among college students, about the importance of risk assessment and risk mitigation through insurance. In addition, many people who are just starting out believe that insurance for children serves as protection and investment. The summary of this activity shows that effective education can increase public awareness and understanding of financial literacy.